Cultural Representation in Oral Folklore The Legend of Babad Alas Prigi: A Literary Anthropology Study - Meinita Istantiani; Murliana Murliana (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2026)
This article examines the oral folklore of the legend of Babad Alas Prigi from an anthropological perspective. The purpose of this study is to determine the form of culture in the legend of Babad Alas Prigi in Trenggalek Regency, East Java. This research is a qualitative study with an ethnographic approach. Primary data was collected by in-depth interviews with cultural experts and reinforced with relevant literature sources. Researchers also used secondary data sources in the form of journal articles and books. Data analysis was carried out descriptively interpretative by processing interview data and narrated comprehensively. The results of the research obtained three forms of culture contained in the legend of Babad Alas Prigi in the form of ideas, activities, and artifacts. The ideas represented in the legend are harmony between brothers, focus on goals, and religiosity. Community activities that are still developing today are the larung sembonyo tradition. Meanwhile, the artifact encountered by the community is the existence of Goa Lawa, which is located in the Watulimo area of Trenggalek Regency. This anthropological study opens new insights for the community regarding the forms of culture that exist in oral tradition.